ANALISIS KEPUASAN PASIEN DI KLINIK HJ. TARPIANIE SIDOARJO - administrator administrator; Elizabeth Murniaty; C. Sri Hartati; Gurendro Putro (Jurnal Manajerial Bisnis, 2018)
The purpose of this study is to determine the quality of service, patient satisfaction, obstacles faced byClinic Hj. Tarpianie Sidoarjo in realizing patient satisfaction. This research is a qualitative research toanalyze patient satisfaction in Clinic Hj. Tarpianie Sidoarjo. Primary data were obtained from in-depthinterviews of patients, doctors, nurses, administrators, and owners Clinic Hj. Tarpianie Sidoarjo. Basedon the results of the research can be known that first, the overall service quality is good enough thisassessment is based on the five indicators of service quality is only one indicator that gets poor penalaian,while the rest get good penilain, good enough, and very good. Second, patient satisfaction in receivinghealth services at Clinic Hj.Tarpiane also considered satisfactory. This conclusion is based on 3indicators of patient satisfaction. The three obstacles that are possessed by the Clinic are as follows: (1)The management is unable to fulfill the patient's wishes, (2) The services provided are not in accordancewith the competence specification (3) the human resources are still incomplete, (4) which does not matchthe patient's expectations. (5) Long and long queues that are not in line with patient expectations.Keywords: patient satisfaction, service quality